IMPLEMENTATION OF SOCIAL MEDIA MANAGEMENT GUIDELINES OF THE DIRECTORATE GENERAL OF IMI-0002. HH.01.01 OF 2022 IN DISSEMINATING INFORMATION AT THE CLASS I IMMIGRATION OFFICE TPI BANDUNG - Mila Rosmaya; G.A Nursanto; T.K Wirajati (Polteknik Imigrasi, 2022)
The Directorate General of Immigration issued a decree regarding the Social Media Management Guidelines for the Directorate General of Immigration, Ministry of Law and Human Rights of the Republic of Indonesia Number: IMI-0002-HH.01.01 of 2022 which contains guidelines for standardizing immigration public information that can be published by all immigration office in Indonesia. This research focuses on the use of social media used by the Bandung Immigration Office to disseminate immigration information, namely Instagram and YouTube. The purpose of this study was to find out the implementation of the directorate general of immigration's social media in disseminating information through social media and recommendations for optimizing Instagram and YouTube social media. The method used in this research is descriptive qualitative research method. The results of this study found that the Bandung immigration office's Instagram and YouTube social media were considered not optimal in implementing the guidelines, there were still deficiencies such as account names that did not comply with the guidelines, color templates used in content, fonts that still adjusted to the uploaded content.